Pengaruh Sikap Perilaku, Keamanan Dan Kerahasiaan Serta Faktor Sosial Terhadap Intensitas Penggunaan E-Filing Wajib Pajak Umkm Kota Metro Dengan Pemahaman Internet Sebagai Variabel Moderasi - Nurindah, Mita; Hendri, Nedi; Darmayanti, Elmira Febri (Universitas Muhammadiyah Metro, 2022)
This study aims to determine the effect of behavioural attitudes, security and confidentiality, as well as social factors, on the intensity of the use of e-filing for MSME taxpayers in Metro City with the understanding of the Internet as a moderating variable. Data obtained from respondents amounted to 95 people. The analytical tes is SmartPLS v.3.3.9 with SEM (Structural Equation Modeling) analysis. The type of research is quantitative. The results showed that social factors significantly positively affected the intensity of e-filing use. Still, behavioural attitudes and security and confidentiality had no impact on the power of e-filing use. Understanding the Internet cannot moderate the influence between behavioural attitudes, security and privacy, and social factors on the intensity of e-filing use.